2017
DOI: 10.1016/j.jpeds.2016.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Duration After Acute Symptomatic Seizures in Neonates: A Multicenter Cohort Study

Abstract: We aimed to define determinants of duration of treatment for acute symptomatic neonatal seizures in a contemporary multicenter observational cohort study. After adjustment for potential confounders, only study site and seizure etiology remained significantly associated with the chance of continuing antiseizure medication after discharge to home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
50
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 15 publications
6
50
0
2
Order By: Relevance
“…Neonates from the initial NSR cohort were previously reported. 2,3,5 Neonates were included if they received a loading dose of an ASM and adequate documentation regarding response to the loading dose was available. Neonates with events that were determined not to be seizures based on history, semiology, or cEEG were not enrolled.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neonates from the initial NSR cohort were previously reported. 2,3,5 Neonates were included if they received a loading dose of an ASM and adequate documentation regarding response to the loading dose was available. Neonates with events that were determined not to be seizures based on history, semiology, or cEEG were not enrolled.…”
Section: Methodsmentioning
confidence: 99%
“…1 Little is known about additional characteristics associated with initial treatment failure, although we previously showed that preterm and term neonates were equally likely to have persistent seizures after a loading dose of phenobarbital 2 and there was no difference in treatment response to initial doses of phenobarbital, phenytoin, or levetiracetam as the first-line ASM. 3 We hypothesized that treatment response to ASMs would not differ by seizure etiology and that treatment response would be dose dependent. Confirming these hypotheses provides important evidence for clinical care and data to inform future clinical trial design.…”
Section: Introductionmentioning
confidence: 99%
“…Table II compares the effect of WP bases selection on the classification accuracy (CA) for ABCD vs E classification based on a 2-fold cross validation. The results showed that the WP coefficients (5,1), (4,1), (4,2) performed better than the other WP basis candidates. Therefore; the WP coefficients (5,1), (4,1), (4,2) were fixed as the best WP bases for all other analyses in this work.…”
Section: Discussionmentioning
confidence: 97%
“…This is arguable since children with DCD might also display persistent difficulties in the acquisition of a variety of other basic gross and fine motor skills (recommendation 2) 3 whereas gross motor skills (recommendation 19, statement 3) 3 are of particular interest in terms of a primary source of environmental stress. 4 Thus, it seems not only questionable whether the selection of tasks within the ALSPAC coordination test facilitates an identification of the entire range of the intended target group (individuals with DCD) but more specifically, whether the partial representation of the problem displayed here is suitable for the elaboration of the environmental context.…”
mentioning
confidence: 96%
“…Hypothermia may never be proven (though stroke cases within the cooling trials have been studied), but euthermia with antipyretics and antibiotics for fever are prudent. These fundamentals are likely to be applicable to the other neonatal stroke syndromes which are increasingly described, but also suffer from the same paucity of evidence.…”
mentioning
confidence: 99%